2009
DOI: 10.1126/science.1178577
|View full text |Cite
|
Sign up to set email alerts
|

Arterial-Venous Segregation by Selective Cell Sprouting: An Alternative Mode of Blood Vessel Formation

Abstract: Blood vessels form de novo (vasculogenesis) or upon sprouting of capillaries from pre-existing vessels (angiogenesis). Using high resolution imaging of zebrafish vascular development we discovered a third mode of blood vessel formation whereby the first embryonic artery and vein, two unconnected blood vessels, arise from a common precursor vessel. The first embryonic vein formed by selective sprouting of progenitor cells from the precursor vessel, followed by vessel segregation. These processes were regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
258
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(278 citation statements)
references
References 26 publications
15
258
2
1
Order By: Relevance
“…One of these studies also reported that Shh and Vegf signaling act upstream of and control Sox7 (Pendeville et al 2008). Interestingly, another recent study has also suggested that there may be selective cell segregation required for proper A-V formation, with distinct steps of cell segregation into arterial and venous fates are controlled by different signaling pathways including VegfA, VegfC, Notch, and Ephrin B2 (Herbert et al 2009). …”
Section: Specification Of Arteries and Veinsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these studies also reported that Shh and Vegf signaling act upstream of and control Sox7 (Pendeville et al 2008). Interestingly, another recent study has also suggested that there may be selective cell segregation required for proper A-V formation, with distinct steps of cell segregation into arterial and venous fates are controlled by different signaling pathways including VegfA, VegfC, Notch, and Ephrin B2 (Herbert et al 2009). …”
Section: Specification Of Arteries and Veinsmentioning
confidence: 99%
“…Netrin1 and its receptor, UNC5B, are required for the proper vessel formation, although conflicting data exist as to whether netrin signaling plays a repulsive role Larrivee et al 2007;Bouvree et al 2008), an attractive role (Navankasattusas et al 2008), or, potentially, both (Yang et al 2007) in the developing vasculature. In addition to their role in arterialvenous specification (Herbert et al 2009), ephrins are also implicated in vascular sprouting in zebrafish. Morpholino knockdown of ephrinB2 causes tip cells to decrease filopodial activity in intersegmental vessels consistent with the observation that ephrin signaling promotes angiogenic activity (Wang et al 1998).…”
Section: Specification Of Tip and Stalk Cells And Keeping Them In Linementioning
confidence: 99%
“…This process involves Rho-dependent kinase and is not known to invoke vesicular trafficking. Another model, termed "selective sprouting," is supported by studies in the developing zebrafish cardinal vein (Herbert et al 2009). The selective sprouting model stipulates that venous endothelial cells migrate from the dorsal aorta to surround erythrocytes and are retained by VEGF-A/VEGFR-2 signaling, a process analogous to vasculogenesis during embryogenesis.…”
Section: Jj Tung Et Almentioning
confidence: 99%
“…The modelling of two major vessels, the dorsal aorta and the cardinal vein, during embryonic development requires repulsive signalling between ephrin-B2 and EphB4 in endothelial cells (ECs) [101,102]. Initially shown in zebrafish [103], and then in mouse [104], the dorsal aorta forms first and harbours a mixed population of venous (EphB4+) and arterial progenitors (ephrin-B2+). Both studies have shown that the formation of the cardinal vein is regulated by repulsive signalling between EphB4 and ephrin-B2.…”
Section: Ephb4 and Ephrin-b2 Function In Normal Human Developmentmentioning
confidence: 99%
“…Signalling between both EphB4 and ephrin-B2 repels venous ECs from arterial ECs generating an EphB4+ cardinal vein [103,104]. During the early stages of embryo development lymphatic ECs differentiate from the cardinal vein and other venous derivatives [105].…”
Section: Ephb4 and Ephrin-b2 Function In Normal Human Developmentmentioning
confidence: 99%